Pengaruh Aplikasi Asap Cair Tempurung Kelapa dan Pupuk NPK Terhadap Hama dan Penyakit pada Padi Gogo - Ahadiyat, Yugi R.; Rostaman, Rostaman; Fauzi, Ahmad (Jurnal Penelitian Pertanian Tanaman Pangan, 2020)
Pest and disease control for the upland rice cultivation needs to be done ecologically with the proper dose of fertilizer. Coconut shell as natural waste can be converted into wood vinegar which is useful for a biopesticide. The application of coconut shell wood vinegar as biopesticide combined with different NPK fertilizer doses needs to be examined in controlling pests and diseases in the upland rice crop. The objective of this study was to know the effect of NPK fertilizer rate and coconut shell wood vinegar application on pests (locusts and leaf folder), and on pathogen infection (Cercospora) on upland rice. The experiment was conducted in Klampok Sub-district, Banjarnegara Regency from April to July 2017. A split plot design was used replicated three times. The main plot was NPK fertilizers viz. 50% and 100% recommendation dosage, and the sub plots were concentration of coconut shell wood vinegar viz. 0% 1%; 1.25%; 1.67%; 2.5% and 5%. The intensity of pest attack, namely locusts and leaf folder, and pathogen infection of Cercospora brown spot disease were observed. Results showed that application of coconut shell wood vinegar suppressed the intensity of locust and leaf folder pests, and lower the intensity of Cercospora pathogen infection. To reduce the intensity of pests and pathogenic infections in upland rice, the application of coconut shell wood vinegar is suggested along with the use of low dose of NPK, for more effective and efficient pest control in environmentally friendly manner.